2015
DOI: 10.1097/mat.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Anti-Xa-Based Anticoagulation Protocol for Patients with Percutaneous Ventricular Assist Devices

Abstract: Because of the complexities associated with anticoagulation in temporary percutaneous ventricular assist device (pVAD) recipients, a lack of standardization exists in their management. This retrospective analysis evaluates current anticoagulation practices at a single center with the aim of identifying an optimal anticoagulation strategy and protocol. Patients were divided into two cohorts based on pVAD implanted (CentriMag (Thoratec; Pleasanton, CA) / TandemHeart (CardiacAssist; Pittsburgh, PA) or Impella (Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…However, this test can be affected by warfarin, high factor VIII due to underlying inflammation, and hemolysis. Recent studies have shown that the APTT underestimates heparin requirements for VAD patients when compared to heparin levels measured by anti‐Xa activity . One of the factors responsible for this discrepancy is residual warfarin effect.…”
Section: Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this test can be affected by warfarin, high factor VIII due to underlying inflammation, and hemolysis. Recent studies have shown that the APTT underestimates heparin requirements for VAD patients when compared to heparin levels measured by anti‐Xa activity . One of the factors responsible for this discrepancy is residual warfarin effect.…”
Section: Management Strategiesmentioning
confidence: 99%
“…Recent studies have shown that the APTT underestimates heparin requirements for VAD patients when compared to heparin levels measured by anti-Xa activity. 90 One of the factors responsible for this discrepancy is residual warfarin effect. It has been shown that for every 1.0unit rise in INR >1, the APTT increases by 16 seconds, which can lead to falsely high APTTs.…”
Section: Anticoagulationmentioning
confidence: 99%
“…Thus anti‐Xa concentrations were proposed as an alternative method for monitoring anticoagulation because better correlations with heparin activity are often observed . The reported reference range for anti‐Xa is 0.3–0.7 units/ml, but alternative goal ranges were previously described during pVAD use (0.15–0.30 units/ml for Impella and 0.2–0.4 units/ml for TandemHeart) …”
Section: Best Practice Recommendationsmentioning
confidence: 99%
“…A retrospective review described the outcomes of an anti-factor Xa (anti-Xa)-based anticoagulation strategy in CentriMag (Thoratec, Pleasanton, CA)/TandemHeart and Impella cohorts. 30 In contrast with the preceding studies, which used only aPTT guidance, this study evaluated anticoagulation practices with both aPTT and anti-Xa concentrations. At the time of the study, the anti-Xa goal range was 0.2-0.4 units/ml, which correlated to an aPTT range of 55-75 seconds.…”
Section: Approaches To Managing Bleeding Riskmentioning
confidence: 99%
See 1 more Smart Citation